2019
DOI: 10.31497/zrzyxb.20190815
|View full text |Cite
|
Sign up to set email alerts
|

Water resources carrying capacity evaluation of the Yellow River Basin based on EFAST weight algorithm

Abstract: this paper calculated the weights using EFAST method, which considers the coupling relationship between indicators. The connection entropy model that can overcome the uncertainty of evaluation was carried out to evaluate comprehensive water resources carrying capacity. By taking the Yellow River Basin as an example, the weights of the carrying capacity indices were calculated using EFAST method and weight entropy method respectively and made a comparison between the two methods. Finally, the water resources ca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
21
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(26 citation statements)
references
References 4 publications
0
21
0
2
Order By: Relevance
“…At the same time, the novel hybrid FCE-AHP-CM approach proposed in this paper has the special superiority in comprehensively dealing with the fuzziness and randomness, and therefore not only could accurately assess the WRCC, but also could significantly increase the robustness and intuition of WRCCA results. In the assessment of the WRCC, this paper and those by Xi [42][43][44][45][46][47][48] found that the WRCC has been effectively improved and showed an increasing trend after the '11th Five-Year Plan' in China. The hydrological conditions such as precipitation have a great influence on the WRCC.…”
Section: Wrcca Results Validation In the Study Areamentioning
confidence: 90%
“…At the same time, the novel hybrid FCE-AHP-CM approach proposed in this paper has the special superiority in comprehensively dealing with the fuzziness and randomness, and therefore not only could accurately assess the WRCC, but also could significantly increase the robustness and intuition of WRCCA results. In the assessment of the WRCC, this paper and those by Xi [42][43][44][45][46][47][48] found that the WRCC has been effectively improved and showed an increasing trend after the '11th Five-Year Plan' in China. The hydrological conditions such as precipitation have a great influence on the WRCC.…”
Section: Wrcca Results Validation In the Study Areamentioning
confidence: 90%
“…The second category of approaches evaluates WRCC using non-integrated assessment methods. Techniques include the normal cloud model (Rabiei et al 2022;Zhang et al 2019), the system dynamics method (Wang et al 2021a;Yang and Wang 2022), and the ecological footprint method (Dai et al 2019). The normal cloud model has symmetric characteristics, and the evaluation cannot reflect the uncertainty in a standardized manner.…”
Section: Literature Reviewmentioning
confidence: 99%
“…In this method, the sensitivity of the model is divided into the sensitivity of the individual parameters acting independently and the sensitivity of the interactions between the parameters. Studies have shown that calculating weights using the EFAST algorithm is more scientific [17]. The EFAST algorithm is completed in SIMLAB software (https://ec.europa.…”
Section: Data Descriptionmentioning
confidence: 99%